2015
DOI: 10.1097/bor.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the origin of non-immune cell-mediated weakness in the idiopathic inflammatory myopathies – potential role of ER stress pathways

Abstract: ER stress pathway activation is clearly of etiological relevance in IIM. Research to better understand mechanisms of weakness downstream of ER stress is now required, and which may discover new therapeutic targets for nonimmune cell-mediated weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Without amelioration of such insult(s) to Ca 2+ homeostasis, Ca 2+ dysregulation progresses in the propagation phase. Mitochondria, susceptible to injury in IBM due to conditions of inflammation, mtDNA abnormalities, and impaired proteostasis, are damaged by excessive Ca 2+ influx [7, 31, 32, 48]. This stimulates ROS production, promoting further Ca 2+ efflux from the SR [15] and ER stress signaling [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without amelioration of such insult(s) to Ca 2+ homeostasis, Ca 2+ dysregulation progresses in the propagation phase. Mitochondria, susceptible to injury in IBM due to conditions of inflammation, mtDNA abnormalities, and impaired proteostasis, are damaged by excessive Ca 2+ influx [7, 31, 32, 48]. This stimulates ROS production, promoting further Ca 2+ efflux from the SR [15] and ER stress signaling [32].…”
Section: Discussionmentioning
confidence: 99%
“…calpain-1), which cleave Ca 2+ -regulatory proteins like SERCA1 [49, 50]. Ca 2+ and redox imbalances in the ER perturb protein folding, inducing UPR signaling [18, 32]. Together, impairment of mitochondrial buffering, degradation of Ca 2+ -regulatory proteins, and suppression of translation cause progressive increases in cytosolic Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…In our article we did not try to imply that the mechanisms of actions of immune cells and ROS generation are mutually exclusive, as clearly inflammatory cell infiltrations are a cause of muscle cell injury and thus weakness. In another recent, and related, review we suggest that inflammatory cell infiltration is in fact a ‘secondary’ feature in IIM 3. We agree that there is likely an interaction between immune cell-mediated and ROS-mediated muscle dysfunction.…”
mentioning
confidence: 51%
“…These findings clearly suggest that myotoxic factors other than immune cell infiltrates are also pathologically involved. Recent reviews have thus suggested that non-immune cell-mediated mechanisms must also play a significant cytotoxic role, over and above that expected from infiltrating inflammatory cells, [7, 8]. Research in human and murine myositis models suggests that chronic over-activation of the ER stress pathway also contributes to weakness induction, [9].…”
Section: Introductionmentioning
confidence: 99%